Estudo da relação entrevariáveis térmicas e o desempenho de estudantes da Academia de Polícia Militar do Estado da Paraíba - Vasconcelos, Priscila Elida de Medeiros (2013)
Air temperature is regarded as an environmental factor with greatest influence on worker performance. However, little information exists about its influence on academic environment. Therefore, this study aims to analyze the effects caused by thermal discomfort on students performance. Thus, students of Military Police Academic Center of Paraíba were subjected to a series of psychometric tests that assessed their reasoning skills in five specific areas: verbal, abstract, mechanical, spatial and numerical reasoning; on three sessions under different temperatures: 20 ° C, 24 ° C and 30 ° C. The optimal temperatures found to thermal sensations and thermal comfort neutrality were approximately 23 ° C and 21 ° C, respectively, which reflects a relatively low thermal preference, compared to that provided by ISO 7730/2005 standard. The performance of students varied according to the nature of the tests. They demonstrated motivation to perform the tests, regardless of which thermal conditions that were subjected. However, with the aid of generalized linear models (GLM), it was found that the dry bulb temperature, globe temperature, and relative humidity influence the overall performance of the students (pseudo-R ² = 0.8497).